Josef Zvěřina and Impulses for Theological Studies – Contemporary Issues - Jana Jičínská (Theology and Philosophy of Education, 2023)
The presented article reflects the perspectives that can be observed in Josef Zvěřina, in his impulses for universities, mission, contribution and continuous spiritual formation of students. An integral part is the contribution and influence of theological thinking on science, culture, human society, and value orientation.